Application of Customer Relationship Management Method On E-Commerce (Case Study : PT Beesge Andalas Perkasa) - Doni Eko Hendro Pramono; Fathurrahman Kurniawan Ikhsan (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
The data processing process related to sales data and the availability of goods currently running still uses conventional recording, namely the absence of a system that can process data automatically to speed up the Customer Relations Management processing process. (CRM) is a method used to simplify the process of communication between consumers and companies in order to create a sense of comfort in consumers towards the company. One proof of the need for a system desired by the owner of PT Beesge Andalas Perkasa is wanting a system that helps promote and introduce his business and also increase sales without even having to cost a lot in the advertising process. The purpose of this study is to help improve the strategy and loyalty of customers and increase the sales power of PT Beesge Andalas Perkasa